Water Productivity Improvement Using Water Saving Technologies in Boro Rice Cultivation (Bangladesh Rice Journal, 2016)
An experiment was conducted at farmers' field aimed to evaluate the water saving technologies in Boro rice. The experiment involved three plots at 33 m, 65 m and 100 m distance from the water source. Each plot was divided into two parts to accommodate two management practices as research management (RM) and farmers management (FM). RM comprised of plastic pipe water distribution system to reduce conveyance loss and alternate wetting and drying (AWD) method for field water management. FM comprised of earthen canal water distribution system and conventional irrigation method. BRRI dhan28 was cultivated with recommended agronomic practices. In RM, irrigation was applied when water level went 15 cm down below the ground surface where FM included conventional practice. Result showed that conveyance loss of water in earthen canal increased with increasing the distance from water source to field. Conveyance loss found 6.1 and 0.5 l s-1 per 100 m in earthen canal and plastic pipe distribution system, respectively. Plastic pipe distribution system successfully minimized 91.6% water loss that occurred in earthen canal. AWD practice alone saved 20.2% field water over conventional practice. Combination of AWD and plastic pipe had saved 42% water, Tk 2,270 ha-1 as electricity cost and Tk 2,947 ha-1 as irrigation cost over farmers management. RM had higher yield than FM due to better performance of yield contributing parameters. Water productivity increased from 0.35 kg m-3 in FM to 0.65 kg m-3 in RM. Both the technologies in RM are environment friendly for reducing groundwater use in the irrigated ecosystem.Bangladesh Rice j. 2016, 20(1): 17-22